2018
DOI: 10.5433/1679-0359.2018v39n5p1957
|View full text |Cite
|
Sign up to set email alerts
|

Microbiology quality, detection of enterotoxin genes and antimicrobial resistance of Staphylococcus aureus isolated from milk and Coalho cheese

Abstract: This study evaluated the microbiological quality of milk and Coalho cheese, the prevalence of enterotoxin genes, antimicrobial resistance and determined an inducible MLSB resistance phenotype by the D-test in strains of Staphylococcus aureus isolated from these products. Seventy samples of milk and Coalho cheese were analyzed. S. aureus strains were identified by biochemical tests. The presence of se genes (sea-see) was tested by polymerase chain reaction. The antimicrobial sensitivity of S. aureus strains was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 21 publications
1
11
3
1
Order By: Relevance
“…Typically, S. aureus SE food poisoning is associated with inappropriate handling of cooked foodstuffs, or improper storage, resulting in bacterial growth and toxin production [ 11 ]. These enterotoxins are mainly found in foods with high amounts of starch and protein, such as meat products, eggs, and dairy products [ 35 , 36 ]; but enterotoxin production is also affected by other factors, such as pH, water activity, temperature. The SEA, SEB, SEC, SED, and SEE classic enterotoxins are responsible for 95% of SFP; with SEA and SED as the most common causes of food poisoning, due to their stability under a wide range of water activities and pH conditions [ 34 , 37 ].…”
Section: Staphylococcus Aureus Exotoxins In Foomentioning
confidence: 99%
“…Typically, S. aureus SE food poisoning is associated with inappropriate handling of cooked foodstuffs, or improper storage, resulting in bacterial growth and toxin production [ 11 ]. These enterotoxins are mainly found in foods with high amounts of starch and protein, such as meat products, eggs, and dairy products [ 35 , 36 ]; but enterotoxin production is also affected by other factors, such as pH, water activity, temperature. The SEA, SEB, SEC, SED, and SEE classic enterotoxins are responsible for 95% of SFP; with SEA and SED as the most common causes of food poisoning, due to their stability under a wide range of water activities and pH conditions [ 34 , 37 ].…”
Section: Staphylococcus Aureus Exotoxins In Foomentioning
confidence: 99%
“…[10] It has been widely reported that the consumption of contaminated food with enterotoxinproducing strains of S. aureus is one of the most common causes of staphylococcal food-poisoning outbreaks worldwide. [11,12] The critical density of S. aureus higher than 10 5 CFU of coagulase-positive S. aureus per gram is required for assumptive enterotoxin production. [7,8,13,14] To date, 24 different staphylococcal enterotoxins (SEc and SEls) have been determined and classified into several evolutionary groups based on a comparison of their nucleotide and amino acid sequences.…”
Section: Introductionmentioning
confidence: 99%
“…Dentro desta grande expectativa da utilização de óleos essenciais para o tratamento de mastites, em substituição ao uso de antibióticos, surge um importante benefício: o fato de evitar a ingestão de produtos lácteos contendo resíduos de antibióticos, o que reduz os riscos à saúde pública (PEREIRA et al, 2018), e também dificulta o processo de aquisição de resistência bacteriana (FERRO; MOURA; GERON, 2016).…”
Section: Resultsunclassified